A surplus based framework for cross-border electricity trade in South America. (May 2019) - Agostini, Claudio A.; Guzmán, Andrés M.; Nasirov, Shahriyar; Silva, Carlos
Abstract: The South American region has experienced a steady increase in its demand for electricity and faces several challenges in the development of the electricity sector. Among them, high fluctuations in hydro generation, high and volatile prices of fossil fuels, and environmental and social impacts associated to energy activities. Strengthening cooperation for cross-border electricity trade is considered a sustainable alternative for addressing these challenges. For the expansion of electricity trade among countries within the region, both infrastructure and a regulation that defines the conditions of the electric power exchanges between countries are required. A good regulatory framework would allow all market players to have access to the commercialization of energy with other countries in the region, guarantee that the treatment of exchanges is non-discriminatory, and maintain the efficiency, cost effectiveness and security characteristics operation of all electricity systems. In this context, this paper proposes a framework with the basic setting conditions for the import and export of energy from the "surplus" available for exchange. The empirical analysis of the regulatory proposal, based on simulations, shows that the exchange of energy from Chile with its neighboring countries is feasible in a clear and transparent manner, reducing the marginal costs of energy and the total cost of operation, keeping the average cost of generation relatively constant. Highlights: South America faces several challenges in the development of the electricity sector. Cross-border energy trade could be a sustainable alternative for addressing energy challenges. A Regulatory proposal for the treatment of short-term power exchanges in South America. Regional trade could reduce the marginal costs in each country and the total cost of operation.